C.1 - Maheshwari, Shriram (New Delhi, 1972)
Consultation is a new but significant dimension of public administration in India, and it is quite permissible to speculate that its impact on the machi nery of government would become deeper in the years to come. This important segment of activities is the theme of Dr. S. R. Maheshwari's Govern ment Through Consultation: Advisory Committees in Indian Government. The author focuses his research on the advisory committees which have been formally called into being to advise the machinery of central government. After enunciating the political philosophy underlying the institution of advisory committees, he traces their growth and development in India and examines as well the factors responsible for their emergence. Although advisory com mittees stand out as highly individualized entities and their classification is none too simple. Dr. Maheshwari classifies all the five hundred and odd advisory committees that are functioning presently at the central level into six categories-consultative committees, expert committees, advisory committees for independent administration, informal consultative committees, territorial com mittees, and zonal councils. The study, moves on to describe and analyze the methods of appointment of commit tees and their members, their terms of reference, their size, the tenure of office of members, the frequency of meetings, etc. In Part II of the book the author takes up for detailed analysis some selected advisory committees from each of the six categories. The last part of the book contains a critical evaluation of the advisory committees.
Keywords: Committees